PENGARUH KETERAMPILAN MANAJERIAL KEPALA SEKOLAH DAN IKLIM KERJA SEKOLAH TERHADAP KINERJA GURU SMA NEGERI SUB RAYON BATANG BARAT KABUPATEN BATANG - Mohamad Arief; Noor Miyono; Muhammad Prayito (LPPM Universitas Cipta Mandiri, 2024)
The aims of this research are (1) to determine the influence of the principal's managerial skills on teacher performance, (2) to determine the influence of the school work climate on teacher performance and (3) to determine the influence of the principal's managerial skills and the school work climate together on teacher performance. The population of this study was 196 State High School teachers in the Batang Barat sub-rayon. The research sample was determined at 130 using a random sampling technique. Validity test, reliability test, normality test, linearity test, multicollinearity test, heteroscedasticity test, single regression test and multiple regression using SPSS for Windows version 25. The research results showed (1) correlation between the managerial skills variable of the principal with high teacher performance with a value of 0.685. The influence of the principal's managerial skills on teacher performance is 46.9% and the remaining 53.1% is influenced by other variables outside the principal's managerial skills. (2) The correlation between school work climate variables and teacher performance variables is weak with a value of 0.353. The influence of the school work climate on teacher performance is 12.5% and the remaining 87.5% is influenced by other variables outside the school work climate. (3) The influence of the principal's managerial skills and school work climate together on the performance of teachers at SMA Negeri Batang Barat sub-rayon is 48.6% and the remaining 51.4% is influenced by variables other than the principal's managerial skills and school work climate.